The forms of informal empire : Britain, Latin America, and nineteenth-century literature - Reeder, Jessie, 1982- (Johns Hopkins University Press, 2020)
"This is a work of comparative literary study that examines the influence of Great Britain's informal empire in Latin America that followed Spain's relinquishment of its New World formal empire. The author finds effects of informal empire (involving maritime trade and markets primarily) in the literary forms of novels, poems, and letters. Britain's informal empire in Latin America lasted from the early nineteenth century until the 1920s"--